Effects Of Aluminium Toxicity On Root Morphology And Physiology Of Two Maize Hybrids - Prasetyo, Teguh (2007)

(untitled)
Acid soils in Malaysia account for 72% of the country that was classified under Ultisols and Oxisols. Crop production is not favorable in highly weathered Ultisols and Oxisols, due to aluminium (Al) and manganese (Mn) toxicities as well as calcium (Ca) and magnesium (Mg) deficiencies. Acid soils with high Al saturation (> 60%) induce water stress and retards plant growth. Al toxicity and water stress affects every aspect of plant growth, including the anatomy, morphology, physiology and biochemistry. Therefore, a detail understanding of the physiological characteristics of Al stress, will lead to improvement of maize (Zea mays L.) with tolerance to Al that can be grown on Ultisols and Oxisols. Three experiments were conducted to study the effects of aluminium toxicity on root morphology and physiology of two maize hybrids (Putra J-58 and C-7). Experiments were conducted in the laboratory and at Field two, Faculty of Agriculture, Universiti Putra Malaysia. The experiments were conducted to study the effect of Al on seed germination, short-term effect of Al on root structure and effect of high Al concentrations on maize growth. The experimental designs were randomized complete block design in factorial arrangement, and replicated three times. Overall results showed that maize seeds were impermeable to Al, even though seeds were soaked in 300 μM Al for 8 h, the seeds when sliced and stained with 0.2% hematoxylin showed that the embryo was not stained. Moreover, seed germination was normal when soaked in Al solution, but after germination, root growth was restricted and root tip became brown, stubby, with lesions on the root surface. The total root length of C-7 was significantly longer than Putra J-58. Hematoxylin staining showed that tolerance level of Putra J-58 was considered as intermediate tolerance to Al, while C-7 was sensitive to Al. Al uptake appears to take place within 30 min, and based on the root morphological observations, Al disrupted root cells within 24 h as indicated by lesions in the cortex tissue of the root tip. High Al concentrations (278 and 556 μM Al) inhibited root growth as well as root branching and induced water stress symptoms. After two days in the Al solution, leaves showed interveinal chlorosis, a symptom of Mg deficiency and supported by result of leaf analysis. This symptom was observed on plant grown in solutions with 278 and 556 μM Al. Ca content in the shoot of maize grown in 0 and 556 μM Al were 8.81 and 4.41 μg/g of DM, respectively. Moreover, Mg content in the shoot of maize grown in 0 and 556 μM Al were 5.51 and 2.33 μg/g of DM, respectively. After six days in the nutrient solution containing 556 μM Al, root and shoot dry matter reduced by 61.1% and 34.8%, respectively, compared to control. In addition, stomatal resistance increased by 84.6% and transpiration rate was reduced 41.8% by 556 μM Al, respectively, compared to control. Al toxicity induced root lesions, stubby roots and deep-cracking on the epidermal tissue of the roots. However, the degree of root inhibition or root damage and the decreasing plant physiological activities were dependent on the level of Al present. Maize root growth appears to show a linear or almost exponential response to Al toxicity.